Emergency management of neck stoma patients during the coronavirus pandemic: a national nurse survey. (24th June 2021) - Senior, Andrew; Chan, Jacquline; Brookes, Kim; Jolly, Karan; Darr, Adnan; Ameen, Rohan
Abstract : Background: Neck stoma patient care involves significant clinical complexity. Inadequate staff training, equipment provision and infrastructure have all been highlighted as causes for avoidable patient harm. Aims: To establish the perception of knowledge and confidence levels relating to the emergency management of neck stomas among UK nurses during the COVID-19 pandemic. Method: A nationwide prospective electronic survey of both primary and secondary care nurses via the Royal College of Nursing and social media. Findings: 402 responses were collated: 81 primary care and 321 secondary care; the majority ( n =130) were band 5. Forty-nine per cent could differentiate between a laryngectomy and a tracheostomy; ENT nurses scored highest (1.56; range 0−2) on knowledge. Fifty-seven per cent could oxygenate a tracheostomy stoma correctly and 54% could oxygenate a laryngectomy stoma correctly. Sixty-five per cent cited inadequate neck stoma training and 91% felt inclusion of neck stoma training was essential within the nursing curriculum. Conclusion: Clinical deficiencies of management identified by nurses can be attributed to a lack of confidence secondary to reduced clinical exposure and education.